2018
DOI: 10.1002/arch.21530
|View full text |Cite
|
Sign up to set email alerts
|

Both farnesyl diphosphate synthase genes are involved in the production of alarm pheromone in the green peach aphid Myzus persicae

Abstract: Farnesyl diphosphate synthase (FPPS) catalyzes the formation of FPP, providing the precursor for the biosynthesis of (E)-βfarnesene (EβF) in plants, but it is unknown if FPPS supplies the precursor for the biosynthesis of EβF, the major component of aphid alarm pheromone, though our previous studies support the hypothesis that EβF is synthesized by the aphid itself. Here, we used two cohorts of the green peach aphid Myzus persicae separately, reared on pepper plant and artificial diet to test the correlations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Interestingly, MpnDV infection increased the titer of EβF significantly. MpFPPS genes were shown to be related to the titer of EβF in the green peach aphid (Cheng & Li, 2019). MpnDV infection up‐regulated the expression level of the MpFPPS1 gene significantly, suggesting MpnDV infection enhanced the titer of EβF in M. persicae by up‐regulation of the gene.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, MpnDV infection increased the titer of EβF significantly. MpFPPS genes were shown to be related to the titer of EβF in the green peach aphid (Cheng & Li, 2019). MpnDV infection up‐regulated the expression level of the MpFPPS1 gene significantly, suggesting MpnDV infection enhanced the titer of EβF in M. persicae by up‐regulation of the gene.…”
Section: Discussionmentioning
confidence: 99%
“…The samples were prepared as described previously (Cheng & Li, 2019). Briefly, the MpnDV‐infected or MpnDV‐free wingless adults (1‐d‐old) were collected and weighed in a 1.5‐ml centrifuge tube ( n = 20) and then comprehensively ground under liquid nitrogen, followed by immediately added to 200 μl hexane.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, FPS has been successfully cloned and studied in various plants. For instance, Chen performed knockdown of FPS genes by using the RNAi technique, and the results showed that the FPS genes are involved in the production of EβF [15]. Closa et al performed knockdown experiments and found that, when FPS is not expressed, embryos appear stalled during early development in Arabidopsis and cause damage to gene inheritance; this suggests that FPS has a critically important effect on Arabidopsis growth and development [16].…”
Section: Introductionmentioning
confidence: 99%